miRNAs and metastasis: little RNAs go a long way - Dykxhoorn, Derek M. (2010)
MicroRNAs (miRNAs) are key regulators of many important biological processes from insulin secretion and fat metabolism to cellular proliferation and differentiation. Given the critical role these small regulatory RNAs play in biology, it is not surprising that the alteration of miRNA expression patterns can have pathogenic consequences. The association between miRNA dysregulation and pathogenesis has been most widely studied in tumorigenesis and a large number of miRNAs have been identified whose expression levels are changed in various tumor types. Although the role that miRNAs play in the development of metastasis is more poorly defined, recent studies have begun to identify miRNAs that can regulate key steps in the metastatic cascade. This review will focus on two emerging stories, the regulation of the epithelial-to-mesenchymal transition (EMT) by members of the miR-200 family and the pleiotropic nature of the metastasis suppressor miR-31.